Persistently elevated alpha-fetoprotein associated with chronic hepatitis B during chemotherapy for malignant ovarian germ cell tumors: a case series and a review of the literature - Xuan Zong; Jia-Xin Yang; Ying Zhang (BMC, 2019)
Abstract Background Alpha-fetoprotein (AFP) plays a crucial role in the management of malignant ovarian germ cell tumors (MOGCTs) and is an important reference index for chemotherapy termination. However, a high level of AFP can also be caused by several benign diseases, causing confusion and impacting treatment decisions. Case presentation We described four patients who were diagnosed with MOGCTs; the histologic subtype in two of them was mixed MOGCTs (yolk sac tumor with mature teratoma), while the rest was immature teratoma. The serum AFP level of each patient was abnormal before surgery, but it was still persistently elevated around 300 ng/ml even after additional cycles of chemotherapy. All patients were thoroughly evaluated, but we did not find any evidence of disease progression or residual tumors. Liver function tests were normal, whereas serum assays revealed positive of hepatitis B surface antigen, and two patients had a high level of HBV-DNA. They were chronic carriers of hepatitis B virus and never received relevant treatments. Then they were managed with tumor surveillance and the antiviral treatment. Thereafter, the AFP levels presented a slowly decreasing trend. Conclusions False elevation of AFP in MOGCTs is a rare condition and should be assessed with a comprehensive evaluation to avoid unnecessary treatments.